Incidence of the mandibular accessory foramina in Brazilian population - Freire, A. R.; Rossi, A. C.; Prado, F. B.; Caria, P. H F; Botacin, Paulo Roberto [UNESP] (My University, 2012)
In adults, the mandibular accessory foramina are variables and are located on the medial surface of the mandible in positions above or below of the mandibular foramen. The aim of this study was to evaluate the incidence of the mandibular accessory foramina in Brazilians human mandibles and discuss the clinical aspects related to the presence of these foramina. Were evaluated 222 mandibles, adults, irrespective of gender. Was observed that 27.93% and 43.24% of the mandibles presented at least one mandibular accessory foramina located on the medial surface in position below and above, respectively, of the mandibular foramen. Unilaterally, the mandibular accessory foramina were observed below and above of the mandibular foramen in 22.07% and 25.22%, of the mandibles, respectively, and 5.85% and 18.02% bilaterally, respectively. This study demonstrated that the incidence of mandibular accessory foramen in the Brazilian population is significant and should be considered in the planning and execution of procedures in several areas of dental clinical practice in order to avoid complications.
Keywords: Accessory foramina; Anatomical variation; Dry mandibles; Incidence